2018
DOI: 10.1002/dc.24121
|View full text |Cite
|
Sign up to set email alerts
|

Adequate at rapid on‐site evaluation (ROSE), but inadequate on final cytologic diagnosis: Analysis of 606 cases of endobronchial ultrasound‐guided trans bronchial needle aspirations (EBUS‐TBNA)

Abstract: Background EBUS‐TBNA is a minimally invasive, reliable technique with high sensitivity and accuracy. ROSE plays a crucial role in triaging specimens to guide management. This study analyzes aspirates that were deemed “adequate” on ROSE, but inconclusive upon final cytologic interpretation. Design EBUS‐TBNAs from 2015 and 2016 were retrospectively reviewed and analyzed for ROSE adequacy versus final cytologic diagnosis. Concurrent and subsequent procedures were evaluated to determine the outcome of ROSE‐adequat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The adequacy assessment for ROSE was in concordance with definitive cytology in all 47 cases (100%). The total time taken for the procedure and the number of passes made in our study were similar to those reported in other studies, and ROSE does not appear to influence these factors 8‐10 …”
Section: Discussionsupporting
confidence: 89%
“…The adequacy assessment for ROSE was in concordance with definitive cytology in all 47 cases (100%). The total time taken for the procedure and the number of passes made in our study were similar to those reported in other studies, and ROSE does not appear to influence these factors 8‐10 …”
Section: Discussionsupporting
confidence: 89%
“…Careful attention to the presence of cilia and cellular uniformity, and absence of mitoses and abnormal nucleoli is necessary to assess a benign diagnosis . Air‐drying artefacts leading to cellular enlargement may be misinterpreted during ROSE . These discrepancies have been reported as difficult cases for cytopathologists.…”
Section: Discussionmentioning
confidence: 99%
“…21 Air-drying artefacts leading to cellular enlargement may be misinterpreted during ROSE. 22 These discrepancies have been reported as difficult cases for cytopathologists.…”
Section: Ta B L E 1 Baseline Features Of the Patientsmentioning
confidence: 99%
“…The usefulness of EBUS-TBNA in the diagnosis of lymphadenopathy in patients without lung cancer has also been reported (4). However, few studies have evaluated the diagnostic results of mediastinal lymphadenopathy using EBUS-TBNA in consecutive patients with or without lung cancer (4,5). The aim of the present study was to analyse the results of the cytological examination using EBUS-TBNA in the diagnosis of mediastinal lymphadenopathy in a single centre, and also discuss the usefulness and diagnostic problems in cytological examination using EBUS-TBNA in patients with mediastinal lymphadenopathy.…”
Section: Introductionmentioning
confidence: 98%